Mapping of Hydrogen Fuel Quality in Europe - Aarhaug, Thor A.; Kjos, Ole S.; Ferber, Alain; Hsu, Jong Pyong; Bacquart, Thomas (Frontiers in Energy Research, 2020)
As part of FCH-JU funded HyCoRA project running from 2014 to 2017, 28 gaseous and 13 particulate samples were collected from hydrogen refueling stations in Europe. Samples were collected with commercial sampling instruments and analysis performed in compliance with prevailing fuel quality standards. Sampling was conducted with focus on diversity in feedstock as well as commissioning date of the HRS. Results indicate that the strategy for sampling was good. No evidence of impurity cross-over was observed. Parallel samples collected indicate some variation in analytical results. It was however found that fuel quality was generally good. Fourteen analytical results were in violation with the fuel tolerance limits. Therefore, eight or 29% of the samples were in violation with the fuel quality requirements. Nitrogen, oxygen and organics were the predominant impurities quantified. Particulate impurities were found to be within fuel quality specifications. No correlation between fuel quality and hydrogen feedstock or HRS commissioning date was found. Nitrogen to oxygen ratios gave no indication of samples being contaminated by air. A comparison of analytical results between two different laboratories were conducted. Some difference in analytical results were observed.